A review of the accessibility of ACT COVID-19 information portals. (February 2021) - Yu, Sarah Yanyue
Abstract: Accessibility of public health websites allows important information to reach as many audiences as possible. This is vital during a public health crisis such as the current COVID-19 pandemic. This paper reviews public health information portals provided by the Australian Capital Territory local government against the Web Content Accessibility Guidelines. Highlights: Official websites need to be accessible for all. The use of the Web Content Accessibility Guidelines. Improvement needed for the use of information technology of the government websites.